THE USE OF COLOR CODING TECHNIQUE TO IMPROVE STUDENTS’ READING COMPREHENSION - Riana, Niar Arta (Jurnal Akademik FKIP Unidayan, 2023)
The problem statement of this research was can the color coding technique improve the students’ reading comprehension in the narrative text in grade XI at SMKN 1 Baubau? The objective of this research was to find out the improvement of students’ reading comprehension in reading narrative text by using the color coding technique in eleventh grade at SMKN 1 Baubau. This research used a pre-experimental method. The population was all eleventh grade students totaling 498 students. The samples were take using simple random sampling totaling 35 students. The data collection in this research was carried out by using pretest and posttest as the instrument . the data obtained were analyzed by descriptive statistics and inferential statistics by SPSS. Based on the results of data analysis, it can be concluded that there is a significant effect of the application of color coding technique to improve students’ reading comprehension of eleventh grade students at SMK Negeri 1 Baubau. The data result show that the sig value is obtained (2-tailed) 0.000 is less than 0.05 (0.000 < 0.05) so that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. It means that there is a significant effect before and after the application of color coding technique, as well as the mean of pre-test and post-test experimental class was 24.43 and 60.29.